Co‐management of communication and care in adolescent and young adult oncology. Issue 10 (19th June 2022) - Sisk, Bryan A.; Keenan, Megan; Kaye, Erica C.; Baker, Justin N.; Mack, Jennifer W.; DuBois, James M.
Abstract: Background: Clinicians have an ethical and practical imperative to engage adolescents and young adults (AYAs) with cancer in communication and care. Many young AYAs have involved parents, but guidelines for co‐management of care with AYAs and their parents are lacking. Methods: We performed 37 semistructured interviews with AYAs aged 12−24 years at diagnosis, recruiting them from two pediatric cancer centers. We performed thematic analysis, aiming to understand how AYAs and their parents navigate their roles in communication and care. Results: We identified six roles that AYAs co‐managed with their parents: (1) managing information, (2) managing social and emotional needs, (3) managing health, (4) advocating and empowering, (5) making decisions, and (6) managing logistics. AYAs tended to take more active roles in managing information and more passive roles in managing logistics, managing health, and making decisions. AYAs described how they and their parents had mutual responsibilities to be strong and to protect other's emotions. Additionally, we identified five factors that influenced AYAs' roles in communication and care: (1) AYA agency, (2) clinician encouragement, (3) emotional and physical well‐being, (4) personality, preferences, and values, and (5) insights and skills. Conclusions: AYAs have nuanced preferences for how they are involved in communication and care roles. Clinicians can help families to clarify their preferences and values around these roles in a way that meets each family's unique needs. Future studies should aim to develop tools that support the fulfillment of these engagement goals.